Nashiruddin al-Thusi’s Contribution to Logic, Ethics, Metaphysics, and the Development of Science - Gusmanedi, Randa; Andriani, Yuli; Armadila, Armadila; Dafrizal, Dafrizal (State Islamic Institute of Palopo, 2025)
This study examines the philosophical contributions of Nashiruddin al-Thusi, one of the most influential figures in Islamic intellectual history. The problem addressed in this research is the limited understanding of al-Thusi’s comprehensive philosophical system, as most existing studies focus only on isolated aspects of his work. The objective of this study is to provide a holistic analysis of al-Thusi’s thought, particularly in the areas of logic, ethics, metaphysics, and science, and to assess its relevance in contemporary contexts. Employing a qualitative descriptive design, the research used a library-based method in which primary and secondary textual sources were systematically collected, categorized, and analyzed thematically. The results show that al-Thusi developed a logical framework that strengthened philosophical reasoning, proposed a tripartite model of ethics that encompassed the individual, family, and society, and advanced metaphysical insights centered on the distinction between necessary and contingent existence. Furthermore, his scientific achievements in astronomy and mathematics, including the development of trigonometry and the formulation of the Tusi Couple, demonstrated his role as both a philosopher and scientist whose work bridged medieval Islamic scholarship with the foundations of modern science. The study concludes that al-Thusi’s integrated vision of reason and revelation provides a coherent model of knowledge that remains relevant for addressing present challenges in education, morality, and the dialogue between science and religion.